Focusguard Student Learning Activity Monitoring System Based on Camera and IoT - Andika Pratama; Apriansyah; Kemas Muhammad Wahyu Hidayat (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
The development of information and communication technology has brought real changes in the world of education, especially in the way the learning process is designed, implemented, and evaluated. Universities no longer only focus on delivering material, but are also required to ensure that students remain actively involved during the learning process. Student involvement is one of the important indicators of learning success because it is directly related to the attention, participation, and quality of students' understanding of the material presented. With that, the researcher utilizes technology which is a solution to help monitor and improve the quality of learning. Information technology, especially the Internet of Things (IoT), allows physical devices to connect with digital systems so that the monitoring process can be carried out in real-time and continuously a monitoring system for student learning activities that is able to work in real-time, is non-invasive, and is easy to implement. Therefore, this study proposes FocusGuard, which is a camera-based student learning activity monitoring system and the Internet of Things (IoT). This system is designed to monitor the general state of classroom activities through visual observation, detect passive conditions in a certain time span, and provide alerts as indicators of declining learning activities. It is hoped that this system can help lecturers and educational institutions in supporting the implementation of smart learning and improving the quality of the learning process in higher education.